Patience of Prince Shiddharta to Enlightenment on Buddha: A Story of Enlightenment Novel (2007) Written by Deepak Chopra: An Individual Psychological Approach - Nugroho, Agung; , Drs. H. Abdillah Nugroho, M.Hum; , Nur Hidayat S.Pd, M.Pd (2015)
The study is purposed to show patience of prince Siddhartha, the main character in Buddha: A Story of Enlightenment to enlightenment. Object of the study of this research is the novel. This research analyses its structural elements and patience of prince Siddhartha that deals with inferiority feeling, striving for superiority, fictional finalism, style of life, social interest, creative power and conscious self using an individual psychological approach. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is taken from the novel and the Notebook written by Deepak Chopra in 2007 while the secondary data sources are other sources related to the primary data. Data collecting method in this study is library research, and in analyzing the data the researcher employs descriptive analysis. The result of the study shows the following conclusion. The structural element of the novel is also offered in a good relation of work in building the story. Based on individual psychology analysis the novel tells that the major character, prince Siddhartha is affected by the psychological effect. Prince Siddhartha with his patience struggling to conquer the lust that control the body and mind to free himself and trying to reach enlightenment.